Hubungan antara massa otot terhadap kekuatan otot abduktor dan adduktor pinggul pada sub-elite atlet renang gaya dada - Marine Sandanairah; Joesoef Roepajadi; Noortje Anita Kumaat; Awang Firmansyah; Panji Bana (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2026)
The main movements in swimming, such as kicking, body rotation, and push-offs from the pool wall, heavily depend on the coordination and strength of the hip muscles. The purpose of this study is to examine the relationship between muscle mass and the strength of hip ABD and ADD muscles in sub-elite swimmers. A total of 33 swimmers, consisting of 20 males and 13 females with characteristics (height 164.30±7.57 cm, weight 56.39±7.58 kg, age 17.36±1.55 years), were involved in the study. Body composition data were obtained using an InBody 270 body composition analyzer, and the data used were skeletal muscle mass (SMM). Meanwhile, ABD and ADD muscle strength was measured using the Force-Frame Strength Testing System. The results of this study indicated a significant relationship between muscle mass and left ADD muscle strength (p-value 0.001 and r-value 0.648), muscle mass and right ADD muscle strength (p-value 0.001 and r-value 0.628), muscle mass and left ABD muscle strength (p-value 0.001 and r-value 0.684), and muscle mass and right ABD muscle strength (p-value 0.001 and r-value 0.655). The results suggest that muscle mass contributes to more specific muscle strength in the hip ABD and ADD muscles, which play a role in maintaining stability during swimming and the breaststroke kick. Further research is recommended to include variations of swimming strokes focusing on other styles and to involve elite athletes to gain a broader understanding of the contribution of muscle mass and muscle strength to swimming performance.